Benin - Health, Nutrition and Population : Health and Poverty Analytical Report - World Bank (World Bank, 2012)
This study is a continuation of the previous sector review, conducted in 2004. The 2008 review had two main objectives. This review is primarily an update on the situation. In its development strategy, Benin gave considerable importance to the health of its population. This effort is part of the long-term vision of the country. Improving health status, especially for the poor, is one of eight strategic directions for that vision. Similarly, on a more operational level, this objective is reflected in the current Growth Strategy for Poverty Reduction (GPRS 2007-2009). Benin is particularly committed towards the Millennium Development Goals, including 3 on the health sector. This review was also an opportunity to further analyze the constraints in the health system, consistent with the new strategy Health Nutrition and Population World Bank, Strategy adopted in 2007. But this exercise was not intended merely to be analytical. It also aimed to enrich the political dialogue between, on one hand, the actors in health and, secondly, the World Bank and other development partners. This effort relates more specifically to some themes such as governance, private sector involvement and alignment of partners' efforts (called technical and financial partners in Benin or PTFs). From this perspective, the journal is also a contribution to Benin's efforts to advance the IHP (International Health Partnership Plus). This initiative is now the main tool for implementing the Paris Declaration. In practice, the journal has sought to contribute to the consensus between the Ministry of Health and the donor group on the diagnosis of the health system and the changes needed to strengthen it. Several guidelines have emerged stronger from this discussion, particularly in the area of governance of the health system. Beyond the reinforcement of the various components of the health system, two fundamental principles should guide the transformation of this system: 1) A principle of corporate governance: through decentralization of the health system, health facilities must have their basic needs better taken into account (hence the need for bottom-up planning) and especially as more independent financially administrative; and 2) A principle of individual governance: health workers should be strongly encouraged to improve their performance (competence, productivity and compliance of patients). Given the limited success of measures to strengthen inspections and other controls "top-down, this incentive can only come from clients, either directly (i.e., bonuses based on cost recovery), or preferably indirectly with a mechanism for payment by results funded by the state and possibly partners.